El Pensamiento Crítico como una herramienta de desarrollo de Liderazgo - Guerrero Bejarano, Maria Auxiliadora (2016)
This study’smain objective is to highlight the importance of critical thinking fromconcept to apply than can be given in decision-making, the use of this type of thinking isassumed to be taught from primary school, but not really everyone can have a real grip on it, canbecome a source of benefits for those who fail to achieve this objective and to act according tothis reasoning, allowing in some cases better results in the pursuit of becoming leaders.